Stress and thermal comfort indexes associated with physiological parameters and energy status in Girolando cows raised on pasture in the tropical savannah (Research, Society and Development, 2020)
This longitudinal observational study was developed to describe thermal stress indexes, the physiological response, and the energy status in Girolando cows raised on pasture in the tropical savannah during the transition and voluntary waiting periods. Twenty Girolando cows were evaluated. The temperature and humidity index (UTI) and the globe temperature and humidity index (ITGU) were measured daily, and cows were assessed and submitted to blood collection at time intervals distributed among the three weeks before calving until the 60th day postpartum. Rectal Temperature, Heart Rate, and Respiratory Rate (TR, FC, and FR) were measured in the morning (6:00 - 8:00 hours) and the afternoon (14:00 - 16:00 hours). TR and FR were used to calculate the Benezra Comfort Index (ICB) and FR to calculate the Iberian Heat Tolerance Index (ITCI). The energy status was evaluated by the levels of glucose, non-esterified fatty acids (AGNEs), beta-hydroxybutyrate (βHB), triglycerides, cholesterol, and HDL. In the period of 8:00 to 16:00 hours, the mean values of ITU ranged from 73.5 to 78.7 and of  ITGU from 81.8 to 88.2, characterizing exposure to thermal stress condition. The variables FC, FR, and TR, differed between morning and afternoon (p